2017
DOI: 10.1128/aac.00311-17
|View full text |Cite
|
Sign up to set email alerts
|

Using Population Pharmacokinetic Modeling and Monte Carlo Simulations To Determine whether Standard Doses of Piperacillin in Piperacillin-Tazobactam Regimens Are Adequate for the Management of Febrile Neutropenia

Abstract: Changes in the pharmacokinetics of piperacillin in febrile neutropenic patients have been reported to result in suboptimal exposures. This study aimed to develop a population pharmacokinetic model for piperacillin and perform dosing simulation to describe optimal dosing regimens for hematological malignancy patients with febrile neutropenia. Concentration-time data were obtained from previous prospective observational pharmacokinetic and interventional therapeutic drug monitoring studies. Nonparametric populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 37 publications
1
31
2
Order By: Relevance
“…Furthermore, higher doses would result in very high peak concentrations, which have been associated with increased prevalence of adverse events such as neurotoxicity . Even though β‐lactams have a wide safety margin and are generally well tolerated, a clear cutoff concentration that defines the risk of neurotoxicity remains unknown . Consequently, alternative dosing strategies are required to increase f T > MIC and ensure sufficient PTA achievement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, higher doses would result in very high peak concentrations, which have been associated with increased prevalence of adverse events such as neurotoxicity . Even though β‐lactams have a wide safety margin and are generally well tolerated, a clear cutoff concentration that defines the risk of neurotoxicity remains unknown . Consequently, alternative dosing strategies are required to increase f T > MIC and ensure sufficient PTA achievement.…”
Section: Discussionmentioning
confidence: 99%
“…10 Even thoughlactams have a wide safety margin and are generally well tolerated, a clear cutoff concentration that defines the risk of neurotoxicity remains unknown. 30 Consequently, alternative dosing strategies are required to increase fT > MIC and ensure sufficient PTA achievement. Because EI only covered MIC 90 when assessing 50% fT > 4× MIC and did not target higher MICs, CI should be strongly considered as first-choice empiric therapy in this population ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The PK models of PIPC and TAZ have been previously described by both one- [16,18,19] and two-compartment models [10,[12][13][14][15]17]. In our study, plasma-concentration-time data were analyzed by a two-compartment model because the AIC values of the two-compartment model (1040.069, PIPC and 596.955, TAZ) were lower than those of the one-compartment model (1063.038, PIPC and 615.059, TAZ).…”
Section: Discussionmentioning
confidence: 97%
“…Some population PK studies concerning PIPC/TAZ in adult subjects have been reported [10][11][12][13][14][15][16][17][18][19]. In many antibiotics, including carbapenems and cephems, elderly patients have been reported to have different PK parameters than younger patients [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation